A quantitative analysis of 3D-cell distribution in regenerating muscle-skeletal system with synchrotron X-ray computed microtomography - Tesařová, Markéta; Mancini, Lucia; Simon, Andras; Adameyko, Igor; Kaucká, Markéta; Elewa, Ahmed; Lanzafame, Gabriele; Zhang, Yi; Kalasová, Dominika; Szarowská, Bára; Zikmund, Tomáš; Novotná, Marie; et al. (Scientific reports, 2018)
One of the greatest enigmas of modern biology is how the geometry of muscular and skeletal structures are created and how their development is controlled during growth and regeneration. Scaling and shaping of vertebrate muscles and skeletal elements has always been enigmatic and required an advanced technical level in order to analyse the cell distribution in 3D. In this work, synchrotron X-ray computed microtomography (µCT) and chemical contrasting has been exploited for a quantitative analysis of the 3D-cell distribution in tissues of a developing salamander (Pleurodeles waltl) limb - a key model organism for vertebrate regeneration studies. We mapped the limb muscles, their size and shape as well as the number and density of cells within the extracellular matrix of the developing cartilage. By using tomographic approach, we explored the polarity of the cells in 3D, in relation to the structure of developing joints. We found that the polarity of chondrocytes correlates with the planes in joint surfaces and also changes along the length of the cartilaginous elements. Our approach generates data for the precise computer simulations of muscle-skeletal regeneration using cell dynamics models, which is necessary for the understanding how anisotropic growth results in the precise shapes of skeletal structures.
Keywords: Synchrotrons; Animals; vývoj svalů; kosterní svaly; regenerace; Urodela; zvířata; X-Ray Microtomography; rentgenová mikrotomografie; Regeneration; synchrotrony; Muscle Development; Caudata; Muscle, Skeletal